A Cotinine in Freeze-Dried Urine Reference Material - Sander, Lane C. (J Res Natl Inst Stand Technol, 1989)
A cotinine in freeze-dried urine reference material (RM 8444) was prepared at three concentrations: (1) a “blank” level typical of nonsmokers with no exposure to cigarette smoke, (2) a “low” level corresponding to nonsmokers with passive exposure to side-stream smoke, and (3) a “high” level typical of smokers. Low- and high-level materials were prepared gravimetrically from pooled urine by the addition of appropriate amounts of cotinine Perchlorate. Cotinine was determined by GC-MS using cotinine-d(3)) as an internal standard. No evidence for sample inhomogeneity was observed. This reference material will fulfill a need for a urine-based standard to assist in the validation of field methods used for assessing exposure to cigarette smoke.